2006
DOI: 10.1080/00015458.2006.11679885
|View full text |Cite
|
Sign up to set email alerts
|

False Aneurysm of the Proper Palmar Digital Artery — Report of a Case

Abstract: A case of false aneurysm of the radial proper palmar digital artery located in the tip of the right index finger is presented. The aneurysm was the result of blunt trauma and the diagnosis was made by contrast enhanced magnetic resonance angiography. The patient was treated by ligation and resection of the aneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A case of false aneurysm of the radial proper palmar digital artery located in the tip of the right index finger was reported by Ballas et al [7]. The aneurysm was the result of blunt trauma and the diagnosis was made by contrast-enhanced magnetic resonance angiography.…”
Section: Handmentioning
confidence: 94%
“…A case of false aneurysm of the radial proper palmar digital artery located in the tip of the right index finger was reported by Ballas et al [7]. The aneurysm was the result of blunt trauma and the diagnosis was made by contrast-enhanced magnetic resonance angiography.…”
Section: Handmentioning
confidence: 94%
“…We found that a preoperative ultrasound scan provided simple, non-invasive confirmation of the suspected diagnosis, and although others have reported success using angiography or magnetic resonance [2,7,8], ultrasound does not need intravenous contrast agents, is patient-friendly, and its near field resolution is superior to that of the other techniques in diagnosing small lesions in the hand. Plain radiographs have been helpful only in cases in which a longstanding aneurysm has caused erosive changes to adjacent bone [9].…”
Section: Discussionmentioning
confidence: 87%